Nonlinear system identification for continuous-time autonomous systems via functional equations methods - Padoan,A; Astolfi,A (IEEE, 2016)
The problem of identifying an autonomous nonlinear system, that is, the problem of finding a state-space description of a given sequence generated by sampling the output of an unknown autonomous nonlinear system, is studied. A theoretical framework which combines the use of the Schroder functional equation with realization-theoretic techniques is developed.